2011
DOI: 10.1080/11250001003680933
|View full text |Cite
|
Sign up to set email alerts
|

Northward spread of tropical affinity fishes:Caranx crysos(Teleostea: Carangidae), a case study from the Mediterranean Sea

Abstract: The blue runner Caranx crysos is a thermophilic species poorly investigated in the Mediterranean Sea. Although considered a typical inhabitant of the southern regions, it has recently established in northwest Sicily and, according to the data presented in this study, is now regularly caught in the central-southern Tyrrhenian Sea up to the Gulf of Naples. Some occurrences of the species were also documented in the Gulf of Taranto (Ionian Sea) and in more northerly localities of the Tyrrhenian Sea, such as Gaeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Remarkably the recent literature is rich in records of these species moving northward with respect to their previously known distribution. In particular, published observations are available for S. viridensis [33], [34], C. crysos [35], [36], S. cretense [37]–[39], C. hyppurus [40], B. capriscus [35], [41]. Moreover, for C. crysos [42], [43] and B. capriscus [44] northward expansions have been also documented in the Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably the recent literature is rich in records of these species moving northward with respect to their previously known distribution. In particular, published observations are available for S. viridensis [33], [34], C. crysos [35], [36], S. cretense [37]–[39], C. hyppurus [40], B. capriscus [35], [41]. Moreover, for C. crysos [42], [43] and B. capriscus [44] northward expansions have been also documented in the Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of carangids, Psomadakis et al . () suggested that the northwards expansion of some species could be related to the increase of floating objects in the Mediterranean, as their juvenile stages have been frequently found associated with fish aggregating devices, drift algae and jellyfish (e.g., Kingsford, ; Massutí et al ., ; Sassa et al ., ). In any case, the current presence of larvae of warm‐water species in the northwestern Mediterranean indicates their successful reproduction in the new distribution areas and confirms the establishment of these species in the cold part of the Mediterranean.…”
Section: Discussionmentioning
confidence: 99%
“…Today, considerable weight is being placed on toxicity effects of EDs on key brain areas causing motor and feeding impairments (Giusi et al 2010), with possible effects on the spread of fish species (Psomadakis et al 2011). Studies have indeed emphasized the importance of standardizing fish behavioral assays as bio-indicators of aquatic contamination.…”
Section: Neurobehavioral Paradigms and Toxicological Concernsmentioning
confidence: 99%